(untitled) (Journal of Philosophy Culture and Political Science, 2022)
The concept of performative theater has recently become increasingly important in the research of cultural and social characters. Conventionally, modern stage performance is considered as a representation of reality, in which one of the fundamental ways of expression is a elastic language with a living presence and a real gesture. The body, physicality and elastic language of a drama theater performer participate in the creation and representation of elastic artistic texts. The author studies the nature and role of the actor’s individual physicality, its influence on the artistic context of the performance. The question of co-authorship of an actor and a director in the creation of artistic texts in a special elastic way is actualized. Through the prism of the intertexuality of the performance, the techniques of representation of the actor’s elastic language are analyzed, where his personal and artistic intertwine together. The issues of representation of elastic language in the structure of dramatic representation in the discourse of actor’s existence are of great importance not only for cultural studies, but also for practical experiments in performative theater. A comparative analysis of the use of elastic language in the performances of the directors of the drama theater of the XX-XXI century helps to track the process of shifting the focus from the director to the actor as a thinker of allegories. In the context of performative theater, the method of representation of elastic language plays an important role, since it actualizes the issue of the actor’s personal search in creating specific ways of expressing the body as a process of organizing a special artistic text.